Pemilihan Tingkat Diskonto untuk Pengukuran Nilai Manfaat Uang pada Proyek Penyediaan Infrastruktur dengan Skema KPBU - Wibowo, Andreas; Zuna, Herry Trisaputra (Institut Teknologi Bandung, 2024)
Abstract Better Value for Money (VFM) is a key reason The Government opts for Public-Private Partnership (PPP) schemes in infrastructure project delivery. The Government has developed a quantitative VFM measurement methodology based on the Public Sector Comparator (PSC). A critical issue within this methodology is determining the appropriate discount rate for PSC and PPP cash flows. This paper aims to evaluate the impact of various discount rates on VFM. Four discount rates are analyzed: the project rate, the risk-free rate, the social discount rate, and a modified project rate. Two approaches are considered: applying the same discount rate and using different rates for PSC and PPP. The findings reveal that differing discount rates, even with identical cash flows, result in variations in VFM. When the same discount rate is applied to both PSC and PPP, the VFM is negative unless the discount rate equals or exceeds the project rate. Moreover, the greater the spread between PSC and PPP discount rates, the lower the VFM when the PSC rate is higher, and the higher the VFM when the PPP rate is higher. This paper recommends the development of more detailed guidelines for determining discount rates to prevent VFM miscalculations, which can result in misleading decisions. Keywords : Value for money, public sector comparator, discount rate, public-private partnership, infrastructure